2010
DOI: 10.1002/adfm.201001878
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Polyesters: Structure–Property Relationships in Thermal Behavior, Ionic Conductivity, and Morphology

Abstract: New bis(ω‐hydroxyalkyl)imidazolium and 1,2‐bis[N‐(ω‐hydroxyalkyl)imidazolium]ethane salts are synthesized and characterized; most of the salts are room temperature ionic liquids. These hydroxyl end‐functionalized ionic liquids are polymerized with diacid chlorides, yielding polyesters containing imidazolium cations embedded in the main chain. By X‐ray scattering, four polyesters are found to be semicrystalline at room temperature: mono‐imidazolium‐C11‐sebacate‐C6 (4e), mono‐imidazolium‐C11‐sebacate‐C11 (4c), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 30 publications
(12 reference statements)
5
97
0
Order By: Relevance
“…Lower T g values were observed for polymers 9 and 10 where the larger [OTf] and [NTf 2 ] anions were employed. The correlation between anion size (network packing) and T g is supported by work previously published by our group as well as by Gibson and could be the result of plasticization and/or ionic interactions [41,42,47]. As expected, an increase in acrylate concentration resulted in an increase in T g for the polymer series 10aee due to the generation of a more highly crosslinked network.…”
Section: Compoundsupporting
confidence: 74%
“…Lower T g values were observed for polymers 9 and 10 where the larger [OTf] and [NTf 2 ] anions were employed. The correlation between anion size (network packing) and T g is supported by work previously published by our group as well as by Gibson and could be the result of plasticization and/or ionic interactions [41,42,47]. As expected, an increase in acrylate concentration resulted in an increase in T g for the polymer series 10aee due to the generation of a more highly crosslinked network.…”
Section: Compoundsupporting
confidence: 74%
“…Because residual water was present in the sample, the stretching for Br" could not be discerned from the FTIR spectrum. Both the NMR and FTIR results were in good agreement with data found in the literatures [53,54]. To recap, the combination of 1 H NMR and FTIR experiments demonstrated that the ionic liquid crystals side chain monomers with different anions were successfully prepared and the anionexchange step was successfully achieved.…”
Section: Results and Discussion 31 Synthesis Of Monomerssupporting
confidence: 78%
“…The ILs examined here exhibit glass transition temperatures between À120 and À75 C with 0.2 nm 3 < V m < 0.5 nm 3 and have lower T g than the alkali inorganic salts [55] with lower V m . Moreover, imidazolium and other organic IL cations can be synthesized with either vinyl, acryl or methacryl groups so that the IL monomers (substituted with polymerizable functional groups) can be easily polymerized to create PILs, which carry an ionic liquid species in each of the repeating units [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Fig.…”
Section: Glass Transition Temperaturesmentioning
confidence: 99%